Investigating the Effectiveness of Developing a Pre-Marriage Educational Package Based on Film Using Sternberg’s Theory on Attitudes About Romance and Mate Selection in Unmarried Girls - Afridon, Mostafa; Kazemian Moghadam, Kobra; Shahbazi, Masoud (Iranian Journal of Educational Sociology, 2022)
Purpose: This study aims to investigate the effectiveness of a pre-marriage educational package based on Sternberg's theory on attitudes about romance and mate selection in single girls. Specifically, it examines the efficacy of a pre-marriage education program for single girls, using Sternberg's theory on love stories. Methodology: This research is applied in purpose, quasi-experimental in method, and uses a pre-test-post-test control group design with a follow-up stage (one month). The statistical population comprised individuals who attended the Haft Sange Zendegi Educational Institute in Izeh city in 2023, selected through available sampling. Fifty single girls were selected and divided into two groups (experimental and control). Before the training classes, both groups were assessed using the Attitudes about Romance and Mate Selection Scale. The experimental group underwent a film therapy program based on Sternberg's concepts for 25 sessions of two hours each, while the control group received no intervention. Data analysis was performed using multivariate analysis of covariance and repeated measures analysis of variance with SPSS 27 software. Findings: The findings indicated that implementing the pre-marriage educational protocol based on Sternberg's theory through film led to a significant shift in the attitudes of single females (P